An Analysis of Code Switching in Song Lyric One Ok Rock - Made, Suamba (Wacana : Majalah Ilmiah Tentang Bahasa, Sastra Dan Pembelajarannya, 2024)
This research focuses on identification the use of code switching in song lyrics from the album “Ambition” used by the Japanese band called One Ok Rock. This research used qualitative method to describe and delivering the data. This research used sociolinguistic as grand theory of code switching to search the meaning, types and function of code switching. Based on the result of the analysis, there are three types of code switching that found in album Ambition by One Ok Rock such as: 1. Tag-switching, 2. Intra-sentential switching, and 3. Inter-sentential switching. There are also four functions of code switching that found in album Ambition such as: 1. Expressive function, 2. Phatic function, 3. Metalinguistic function, and 4. Poetic Function. The result of the research conducted, found data in the form of types of code switching are 18 data and 16 data was found in form of the functions of code switching, so that the total number of data found was 34 data.